DISCOURSE ANALYSIS OF TEACHER’S SPOKEN LANGUAGE IN ENGLISH CLASS OF SMPN 16 PALANGKA RAYA - Roliani, Chintia Monica; Asi, Natalina; Luardini, Maria Arina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2020)
The research was conducted using qualitative research method with one English teacher of SMPN 16 Palangka Raya as the subject of the study, and the objectives are to analyse (1) the teacher’s use of spoken English in her instruction referring to the Lesson Plan, (2) the structure used by the teacher, (3) the vocabulary used by the teacher. The data were obtained from class observation and interview with the teacher. The result of data analysis and the discussion of the findings show several matters related to the teacher’s spoken language in English class of SMPN 16 Palangka Raya as follows : (1) The teacher’s use of English Instruction was appropriate with the Lesson Plan, which included orientation, apperception, motivation, and giving references; (2) the teacher used English spoken language at first and then followed by Indonesian due to the students’ weakness in English; (3) the teacher used simple vocabulary, which all of them were used to make the condition of the classroom alive and give relaxing atmosphere that the teacher’s utterances could be easily understood by the students.